Sustainable Urban Development and Social Sustainability in the Urban Context (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
Social sustainability and sustainable urban developments are major challenges across the world both developed and developing countries. In general there is a conflict between the approach of sustainable development and social sustainability in the urban context. The concept of sustainability brings a key framework for extensive literature on urban design, architecture and planning. Nevertheless there is a considerable overlap between the social dimensions of sustainability and the theories or notions, for instance the ‘sustainable societies’ that are highlighted in the midst of other aspects: social equity and justice. Such society is widely expected to offer a situation for long-term social relations and activities which are sustainable, inclusive and equitable in a wider perception of the term (environmentally, socially and economically). The method adopted to address this aim involves a content analysis of available academic literature, with focus on the planning sustainable development, built environment, social sustainability, and urban planning fields. The findings demonstrate that in spite of some opposing evidence, many studies have confirmed that there has been displacement of the debate on the term of ‘sustainability’ from ‘ecological and environmental aspects into social and economic aspects’. It is related to how the community feel safe and comfortable living in their own communities, how have they felt of proud of the place where they live. The aim of the paper is to improve our understanding of current theories and practices of planning sustainable development and discuss whether the approach of sustainable development aligns with social sustainability objectives.